The Role of The UN in the Maintenance of International Peace and Security Case Study: The 2003 War in Iraq - LAMIA, BOUABDALLAH (Journal of Ecohumanism, 2026)
The mission of the United Nations is to restore peace around the world, to end wars, and to resolve conflicts between states. Peace is the primary objective of the UN ; however, many conflicts remain unresolved by the UN. For example, the UN had been unable to prevent the Iraq War, the Russian invasion of Ukraine and conflicts in the Middle East. In the 1950’s and 1960’s, the UN was considered as the leader of the world as it helped countries in Africa and Asia to win their independence. For example, it was the savior of South Africa in its fight against racism, particularly the Apartheid regime. Nowadays, millions of people are killed by unjustified wars, and the world is endangered by the proliferation of these conflicts, all of which the UN was unable to hinder. The American invasion of Iraq without the United Nation’s permission was a defeat for this organisation in face of American military aggression, and the UN’s decline became clear in its incapacity to stop the Iraq War. This research will clarify the notion of peace and security within the United Nations, focusing on the UN’s role in providing international peace and security.